(untitled) - Stopka, Ondrej; Sulgan, Marian (Doprava a spoje, 2012)
The paper deals with the brief characteristics of combined transport in general, the history of combined transport in the Slovak Republic and its advantages. There are also mentioned current measures for the combined transport development and specifics of intermodal terminals in Slovakia. At the end of the article, the proposal of appropriate measures necessary for the combined transport development in the Slovak Republic is outlined.